Students' Mastering of Structural Analysis of Substance as a Method to Form Future Specialists' Scientific Thinking. Part II - L. A. Baikova; M. A. Kosareva; E. A. Nikonenko; V. V. Vaitner; A. Majee (Russian State Vocational Pedagogical University, 2019)
Introduction. In today's knowledge society, the amount of scientific-applied information, which university graduates have to acquire, continues to increase continuously. There is a concurrent reduction in the number of study hours to undertake educational programmes in order to increase the hours for students' independent work. Against this background, higher school is required to increase future experts' competencies. Therefore, the content of fundamental and special disciplines of entire period of training and independent work of students should be thoroughly coordinated by increasing students' motivation to self-education and self-development. Classroom-based and independent learning of disciplines and sections of fundamental academic courses, especially chemistry, is impossible without formation of students' scientific thinking. Today, it is difficult to consider the activity of most professionals without the ability to think scientifically: active expansion of science into professional sphere has a strong tendency to be increased.The aim of the present research is to show the possibilities of formation and development of scientific thinking in the students of natural-scientific and technical directions of education using the example of studying of one of the elements of programmes in chemistry (the method of nuclear magnetic resonance (NMR) analysis).Methodology and research methods. The research was carried out on the basis of competency-based, systematic and interdisciplinary approaches. The methods of analysis, synthesis, integration, differentiation and compactification of fundamental knowledge and training material were used.Results and scientific novelty. The high potential of chemical education for formation of scientific thinking, subject content (chemical), natural-scientific and holistic scientific thinking is emphasised. However, chemistry education in higher education institution is complicated by the absence of the unified structure of fundamental preparation, the preservation of extensive approach to the content of chemical disciplines, the irrational organisation of students' independent work, which now is accounted for a half of instructional time. Overcoming these problems lies in the dialectic unity of fundamental and practice-oriented knowledge, which is provided by the compliance with the principles of continuity and interdisciplinarity. It is necessary to provide deductive structurisation of training material in order to give integrity and systemacity to the content of education, without which it is impossible to create a comprehensive natural-scientific picture of the world in students. The key initial element of vocational training stimulating the formation of reflexive skills and scientific thinking of future experts is mastering by students of a categorical-conceptual framework of science, which is consistently and comprehensively revealed throughout a high school stage of education. The authors designated phases of development of scientific thinking (formal-logical, reflexive-theoretical, hypothetico-deductive thinking), which are not clearly differentiated due to interpenetration and entanglement of their components and identity of thought processes in terms of their speed and quality. However, the allocation of these stages allows to structure and to correct the content of educational material taking into account the characteristics and the level of students' readiness.From these standpoints, the expediency of more detailed examination of the NMR method is proved within the disciplines such as "Chemistry", "General Chemistry", "Inorganic Chemistry" and "Analytical Chemistry" (a part of material about the NMR method can be worked out by students independently). This method, based on one phenomenon, includes hundreds of various types of the experiments, which are intended for receiving particular information. The NMR method is widely used both in scientific research, including master's thesis, and in the most various manufacturing spheres. Today, the spectroscopy of NMR is recognised as the most powerful informative and perspective method of structural analysis of substance. The fundamental nature, interdisciplinarity and universality of the method provide students with basic professional knowledge on physics, chemistry, medicine, biology, technology and ecology. The authors of the present research propose the option of configuration of educational information on NMR. According to the suggested version, the principle of work is the following: firstly, bachelors study the system of key concepts and terms, moving gradually from formal-logical to substantial generalisations; then, students learn to explain the phenomena scientifically and to make forecasts, and, as a result, they become the "owners" of hypothetico-deductive thinking. The acquired competencies are the key to professional literacy, which is improved in master's degree programme, when the previously compactified scientific knowledge in a contracted form is developed in the form suitable for an optimal solution of a particular research or practical aim. The similar scheme of vocational training makes it possible to overcome traditional orientation of high school programmes of the natural-science block (i.e. retention of permanently growing amount of factual material).Practical significance. The research materials can be useful for methodologists of the higher school, for experts engaged in methodological development and the organisation of educational process, for high school teachers of chemistry and related disciplines, for post-graduate students and master's students of chemical and chemico-technological specialties as well.